КОМУНІКАТИВНИЙ АСПЕКТ БРИТАНСЬКОЇ ФОЛЬКЛОРНОЇ П’ЄСИ - Холмогорцева, І.С. (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 1970)
У статті розглядається дискурс британської фольклорної п’єси як комунікативно-пізнавальна система. Пропонується багатофакторна модель опису, метою якої є виявлення специфіки організації фольклорного дискурсу, а саме, соціокультурний компонент і комунікативні фактори (мета, ситуація, комуніканти). Ключові слова: британська фольклорна п’єса, соціокультурні і комунікативні фактори, фольклорний дискурс.  Холмогорцева И.С. Коммуникативный аспект британской фольклорной пьесы. В статье рассматривается дискурс британской фольклорной пьесы как коммуникативно-познавательная система. Предлагается многофакторная модель описания, целью которой является выявление специфики организации фольклорного дискурса, а именно, социокультурный компонент и коммуникативные факторы (цель, ситуация, коммуниканты). Ключевые слова: британская фольклорная пьеса, социокультурные и коммуникативные факторы, фольклорный дискурс.  Kholmogortseva I.S. Communicative Aspect of British Folk Play. The article deals with the discourse of the British folk play as a communicative and cognitive system. There has been offered a multifactor model that aims at revealing the peculiarities of folklore discourse organization, namely, social and cultural components and communicative factors (purpose, situation, communicators). Key words: British folk play, social, cultural and communicative factors, folklore discourse.